Weight Loss Exercise: Knowledge, Attitudes And Practices Among Nursing Students In Kuala Terengganu Nursing College - Norli Abd Rahman; Chan , Siok Gim (Lincoln University College, Asia Pacific Higher Learning Sdn Bhd, 2018)
Exercise is an important practice in leading a healthy lifestyle. However, recently the percentage of Malaysians who practice healthy lifestyle has decreased and the rate of overweight or obesity is increasing. This study aims to explore the knowledge, attitudes and practices of exercise among nursing college students. Questionnaires were used as a research instrument and distributed to Kuala Terengganu Nursing Collage students consisting of 281 students, ranging from year 1 to year 3 in semester II. Data collection was carried out within two weeks. The results of this study showed that almost 66.9% of trainees chose aerobic exercise as their favorite exercise. This form of exercise is good for strength and durability of the cardiovascular. Almost 90.4% of them did exercises together with their friends. From the results, their coach had a relatively good level of knowledge about exercise. The majority of students have a positive attitude towards exercise. There is a relationship between knowledge and their value of exercise. Age is correlated with knowledge, meaning that the older the person the more knowledgeable they are on the benefits of exercise. Age and semester of study showed moderate correlation of 0.525 with awareness of exercises to increase stamina and strength of the body's defenses. (Abstract by authors)